A Multiple processing hybrid flow system for analysis of formaldehyde contamination in food - Teerasong S. (2014)
This work proposes a flow system suitable for the rapid screening of formaldehyde contaminated in food. The system is based on the concept of a flow analyzer with a Hantzsch reaction. An operating procedure was developed for multiple tasking and high sample throughput. This resulted in a significant sample throughput of 51 samples h-1. Under the optimized conditions, linear calibration from 10 to 100 μM was obtained. The system gave a limit of detection and a limit of quantitation of 0.06 and 0.10 mg kg-1, respectively. The system was successfully applied to re-hydrated dry squids, vegetables and mushrooms. 2010 © The Japan Society for Analytical Chemistry.